2015
DOI: 10.1093/neuonc/nov155
|View full text |Cite
|
Sign up to set email alerts
|

Loss of endothelial programmed cell death 10 activates glioblastoma cells and promotes tumor growth

Abstract: For the first time, we provide evidence that loss of endothelial PDCD10 activates GBM cells and promotes tumor growth, most likely via a paracrine mechanism. PDCD10 shows a tumor-suppressor-like function in the cross talk between ECs and tumor cells and is potentially implicated in GBM progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 34 publications
2
42
0
Order By: Relevance
“…Synthetic biological functions of PDCD10 warrant more investigation. In contrast to the well-established mechanism of PDCD10 in vessel permeability and neo-angiogenesis, limited information about PDCD10 in cancer research has been reported (35,36). He et al (37) forecasted that PDCD10 may play an important role in cancer since it can influence angiogenesis by targeting vascular endothelial growth factor receptor 2 (VEGFR2) (37).…”
Section: Discussionmentioning
confidence: 99%
“…Synthetic biological functions of PDCD10 warrant more investigation. In contrast to the well-established mechanism of PDCD10 in vessel permeability and neo-angiogenesis, limited information about PDCD10 in cancer research has been reported (35,36). He et al (37) forecasted that PDCD10 may play an important role in cancer since it can influence angiogenesis by targeting vascular endothelial growth factor receptor 2 (VEGFR2) (37).…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA extraction, cDNA synthesis and RT 2 ‐PCR were performed as previously described . The primers and the annealing temperature for individual genes are listed in Table (Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA extraction, cDNA synthesis and real-time RT-PCR (RT 2 -PCR) Total RNA extraction, cDNA synthesis and RT 2 -PCR were performed as previously described. 20 The primers and the D Pierscianek et al…”
Section: Patientsmentioning
confidence: 99%
“…Table 1 Recently discovered pro-and anti-angiogenesis factors Pro-angiogenesis TGLI1 [63], H19 [51], C/EBPbeta [14], MCSF [15], annexin A2 [39], CXCR4 [66], Oct-3/4 [16], miR-31 [50], miR-148a, HSP47 [38] Anti-angiogenesis hHSS1 [29], NNC55-0396 [30], TTAC-0001 [67], calpastatin [68], miR-137 [65], EZH2 [65], BMP7v [31], PDCD10 [32], JSI-124 [33] Brain Tumor Pathol…”
Section: Resultsmentioning
confidence: 99%
“…Because of the loss of programmed cell death 10 (PDCD10), some proangiogenic factors decreased. It is credible that PDCD10 may show anti-angiogenesis-like function in GBM [32]. Moreover, JSI-124 is demonstrated effectively to inhibit GBM angiogenesis and invasion [33].…”
Section: Angiogenesis In Gbm and Anti-angiogenic Therapiesmentioning
confidence: 97%